A Study of Student’s Anxiety in Speaking Skill A Case Study in Islamic Criminal Law Student - Amir Hamzah (Institut Agama Islam Darussalam Blokagung Banyuwangi, 2021)
AbstractThis study aims to describe about the elements cause students’anxiety in speaking skill and the students strategies to cope the anxiety in speaking skill at Syaichona Cholil Bangkalan Islamic in Islamic Criminal Law Major Student of first semester in academic year 2021-2022 as participants. There are 22 students as participants researcher take by purposive sampling. Researcher also take 3 students in class of Medical Record. Descriptive Qualitative was used in this study. The data were through structured Interviews and classroom observations. The data were describe by interview transcripts. The result of this study describe three elementss that cause students’ anxiety in speaking English. The first is Self Perception of students that always feel English is difficulty to Learn and speak also there a lot of referencees in English Language related to Islamic Criminal law Students’s. The second elements is Class Condition of Performance make students got anxiety when they speak in front of their friends and lecture. The third is students’ Anxiety in speaking English is Fear of Making Mistakes. The result of this study also found there are three strategies that students used to cope the anxiety in speaking English. The first is Preparation, eight students did preparation always felt better before speaking English. The second is Positive thinking, seven participants did positive thinking can cope the anxiety in speaking English. The last is Relaxation, there five students take this strategie if students feel anxiety and failed speaking English.